2017
DOI: 10.1159/000464325
|View full text |Cite
|
Sign up to set email alerts
|

Allergens of <b><i>Blomia tropicalis</i></b>: An Overview of Recombinant Molecules

Abstract: Allergic diseases are considered a major problem for healthcare systems in both developed and developing countries. House dust mites are well-known triggers of allergic manifestations. While the Dermatophagoides genus is widely distributed globally, Blomia tropicalis is the most prominent mite species in the tropical and subtropical regions of the world. Over the last decades, an increase in sensitization rates to B. tropicalis has been reported, leading to increased research efforts on Blomia allergens. In fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 99 publications
3
31
0
4
Order By: Relevance
“…Here we showed that short-term treatment with low dose of allergens and CpG efficiently reduced key features of allergic asthma. In addition, we also evaluated whether this type of immunotherapy could be applied to a relevant respiratory allergens obtained from B. tropicalis mite extract, one of the most prevalent mites in tropical countries (78) and found that the treatment with co-encapsulated Bt allergens and CpG reversed the established allergic lung responses. These results demonstrate the potential applications of our formulation to different allergens and highlight the importance of correct diagnosis for developing a specific allergen treatment (79).…”
Section: Discussionmentioning
confidence: 99%
“…Here we showed that short-term treatment with low dose of allergens and CpG efficiently reduced key features of allergic asthma. In addition, we also evaluated whether this type of immunotherapy could be applied to a relevant respiratory allergens obtained from B. tropicalis mite extract, one of the most prevalent mites in tropical countries (78) and found that the treatment with co-encapsulated Bt allergens and CpG reversed the established allergic lung responses. These results demonstrate the potential applications of our formulation to different allergens and highlight the importance of correct diagnosis for developing a specific allergen treatment (79).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to emphasize that the Blo t 5 molecule has a low cross-reactivity with the Der p 5 allergen and can be suggested as asthma biomarker in tropical regions [120]. The same study showed that true co-sensitization to D. pteronyssinus and Blomia allergens resulted in a higher risk of asthma.…”
Section: Mite Allergens and Asthmamentioning
confidence: 97%
“…Blo t 5 and Blo t 21 share a moderate degree of homology, but the IgE cross-reactivity between the 2 allergens is very limited [24-26]. Thus, Blo t 5 or Blo t 21 are defined as BTMA [27, 28]. In this study, the BTMA+ group, with specific IgE to either Blo t 5 or Blo t 21, was denoted as “co-sensitized”; the BTMA– group, where patients had no detectable IgE to neither Blo t 5 nor Blo t 21, was denoted as “cross-reactive” to DP.…”
Section: Introductionmentioning
confidence: 99%